Analysis of Irrigation Water Requirement in Batang Sanipan 2 Irrigation Area Limapuluh Kota Regency - Arbi, Yaumal; Jamarun, Novirman; Sumbara, Bagas (CIVED, 2023)
Limapuluh Kota Regency is one of the rice producing districts in West Sumatra Province, so an irrigation network is needed to meet water requirement for agricultural productivity. The problem that occurs in the Batang Sanipan 2 irrigation area is the inability of water to flow through the service area to the end point of the irrigation area. Based on observations from e-PAKSI data from the Limapuluh Kota Regency Public Works Office, water can only flow up to a distance of 3.175 km from the intake gate and experience water loss along 1.445 km to the end of the canal. Therefore, it is necessary to study the analysis of irrigation water requirement in the irrigation area of Batang Sanipan 2, Limapuluh Kota Regency. This type of research is descriptive with a quantitative approach. Research methods carried out directly in the field. Based on data analysis, the results obtained from the manual calculation of KP – 01 the maximum irrigation water requirement with a value of 0.139 m3/second which occurred in March, while in the Cropwat software the maximum irrigation water requirement with a value of 0.149 m3/second which occurred in July. The results of measuring the discharge at the intake of the Batang Sanipan 2 weir obtained a discharge of 0.378 m3/second. Based on this, water is sufficient to flow through the entire agricultural area of the Batang Sanipan 2 irrigation area, but the current conditions are that water is not able to flow through parts of the Batang Sanipan 2 irrigation service area.